(untitled) (Applied Biological Research, 2023)
A number of microsporidia have been reported as infecting the gut of silkworm and then passing to the other organs via gut wall (Kawarabatta, 2003; Bhat, 2006). However, in most cases such reports have been dealt more with the development of microsporidians with little emphasis on host parasite interaction. Microsporidia (Msp) isolated from economically important insect silkworm, Bombyx mori infects the cytoplasmic cells of gut causing histopathological alterations (Kamili et al., 2009, 2010). This paper describes the ultrastructural histopathological changes observed in microspordian infected tissues of the silkworm.